Met his every goal? : James K. Polk and the legends of Manifest Destiny - Chaffin, Tom (The University of Tennessee Press, 2014)
Soon after winning the presidency in 1845, according to the oft-repeated anecdote, James K. Polk slapped his thigh and predicted what would be the "four great measures" of his administration: the acquisition of some or all of the Oregon Country, the acquisition of California, a reduction in tariffs, and the establishment of a permanent independent treasury. Over the next four years, the Tennessee Democrat achieved all four goals. And those milestones & mdash;along with his purported enunciation of them & mdash;have come to define his presidency. Indeed, repeated ad infinitum in U.S. history textbooks, Polk's bold listing of goals has become U.S. political history & rsquo;s equivalent of Babe Ruth & rsquo;s called home run of the 1932 World Series, in which the slugger allegedly gestured toward the outfield and, on the next pitch, slammed a home run. But then again, as Tom Chaffin reveals in this lively tour de force of historiographic sleuthing, like Ruth's alleged "called shot" of 1932, the "four measures" anecdote hangs by the thinnest of evidentiary threads. Indeed, not until the late 1880s, four decades after Polk & rsquo;s presidency, did the story first appear in print. In this eye-opening study, Tom Chaffin, author, historian, and, since 2008, editor of the multi-volume series Correspondence of James K. Polk, dispatches the thigh-slap anecdote and other misconceptions associated with Polk. In the process, Chaffin demonstrates how the "four measures" story has skewed our understanding of the 11th U.S. president. As president, Polk enlarged his nation's area by a third & mdash;thus rendering it truly a coast-to-coast continental nation-state. Indeed, the anecdote does not record, and effectively obscures complex events, including notable failures & mdash;such as Polk's botched effort to purchase Cuba, as well as his inability to shape the terms of California's and the New Mexico territory's admission into the Union. Cuba would never enter the federal Union; and those other tasks would be left for successor presidents. Indeed, debates over the future of slavery in the United States & mdash;debates accelerated by Polk's territorial gains & mdash;eventually produced perhaps the central irony of his legacy: A president devoted to national unity further sectionalized the nation & rsquo;s politics, widening geopolitical fractures among the states that soon led to civil war. Engagingly written and lavishly illustrated, Met His Every Goal? & mdash;intended for general readers, students, and specialists & mdash;offers a primer on Polk and a revisionist view of much of the scholarship concerning him and his era. Drawing on published scholarship as well as contemporary documents & mdash;including heretofore unpublished materials & mdash;it presents a fresh portrait of an enigmatic autocrat. And in Chaffin's examination of an oft-repeated anecdote long accepted as fact, readers witness a case study in how historians use primary sources to explore & mdash;and in some cases, explode & mdash;received conceptions of the past. Tom Chaffin is research professor at the University of Tennessee, Knoxville, for which he directs and edits the multi-volume series Correspondence of James K. Polk. He lives in Atlanta and is the author of, among other books, Giant's Causeway: Frederick Douglass's Irish Odyssey and the Making of an American Visionary, Pathfinder: John Charles Fr & eacute;mont and the Course of Empire, and Sea of Gray: The Around-the-World Odyssey of the Confederate Raider Shenandoah